Investigating the use of non-contact infrared thermometers in cats and dogs. (2nd March 2019) - Hall, Emily J; Fleming, Aisling; Carter, Anne J
Abstract : Background: Non-contact infrared thermometers (NCIT) provide a quick, hands off method of monitoring patients' body temperature. There are now animal specific NCIT devices available, however evidence for their use is currently lacking. Aims: To evaluate the accuracy of two animal NCIT devices when compared with rectal temperature in anaesthetised cats, and ear temperatures in exercising dogs. Methods: 27 cats undergoing routine neutering under anaesthetic, and 30 dogs competing in cross country races were recruited to the study. Ocular surface temperature was measured with each of the NCIT devices and compared with rectal temperature (in cats) or ear temperature (in dogs). Findings: Less than a third of the readings from both NCIT devices reported temperatures within 0.5°C of rectal temperature (in cats) and ear temperature (in dogs). Conclusion: The animal specific NCIT devices do not accurately report body temperature in cats or dogs, so their use in clinical situations cannot be recommended.